Implementasi Sistem E-Surat Digital Untuk Pelayanan Administrasi Surat Di Balai Desa Pringtulis - Maharani, Vanessa; Prasetyo Utomo, Andy (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2026)
Letter administration services at the Pringtulis Village Office currently run conventionally, causing long processing times, queues, and a lack of submission tracking. This activity aims to implement a Digital E-Letter system to solve these bureaucratic problems and improve service efficiency. System development uses the SDLC Waterfall method, where requirements were analyzed using observation, interview, and documentation methods. The implementation results show that this web-based system significantly simplifies the bureaucratic workflow. Residents can apply for letters independently (paperless) through Population Identification Number (NIK) validation without account registration. The implementation of a Digital Signature (TTD) by the Village Head effectively cuts processing time from days to hours. The tracking feature and independent PDF downloads validated with QR Codes provide accessibility, document authenticity, and service transparency. This governance transformation successfully creates faster, more efficient, transparent, and responsive village public services.